2015
DOI: 10.1007/s00520-015-3060-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the treatment of chronic chemotherapy-induced peripheral neuropathy using long-wave diathermy and interferential currents: a randomized controlled trial

Abstract: This study provides no support for the use of a combination of long-wave diathermy and ITH as a treatment option for patients with chronic CIPN. However, the chronic CIPN symptoms decreased with time irrespective of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
14
1
1
Order By: Relevance
“…Almost half indicated that they did not use electrotherapy techniques at all in the management of CIPN. This is in contrast to what is reported in the literature where the use of long-wave diathermy, interferential currents (Lindblad et al 2016) and PBM (Argenta et al 2017) are reported to be beneficial in the treatment of CIPN.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Almost half indicated that they did not use electrotherapy techniques at all in the management of CIPN. This is in contrast to what is reported in the literature where the use of long-wave diathermy, interferential currents (Lindblad et al 2016) and PBM (Argenta et al 2017) are reported to be beneficial in the treatment of CIPN.…”
Section: Discussioncontrasting
confidence: 99%
“…The physiotherapy management of CIPN has not been researched extensively. From an in-depth literature search, it was found that internationally, the most frequently used physiotherapy management strategies are: manual therapy techniques, such as massage (Brami, Bao & Deng 2016), neuro-developmental techniques, such as sensorimotor retraining (Duregon et al 2018), cardiopulmonary therapy, such as breathing exercises and lifestyle modification (Derksen et al 2017), therapeutic exercises (Kleckner et al 2017) and electrotherapy modalities, such as diathermy, transcutaneous electrical nerve stimulation and photobiomodulation (PBM) (Freitas de Freitas & Hamblin 2016;Lindblad, Bergkvist & Johansson 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the eligibility assessment 520 articles were excluded. Ultimately, a total of 18 completed studies published between 2000 and 2020 were included in the present review [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The selection process is illustrated in Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Interferential therapy is another electrophysical treatment, in which electrical stimuli are applied on the painful area via two or four electrodes using medium-frequency alternating current (MFAC) at frequencies between 1 and 1500 Hz [46,47]. Lindblad et al studied the therapeutic effect of interferential therapy and long-wave diathermy as a monotherapy in patients with chemotherapy-induced painful polyneuropathy and found that long-wave diathermy at low power is effective in decreasing the pain intensity whereas the combination of interferential therapy and long-wave diathermy at high power is not [33].…”
Section: Transcutaneous Electrical and Electromagnetic Stimulationmentioning
confidence: 99%